Genetic susceptibility to airway inflammation and exposure to short-term outdoor air pollution - Femke Bouma; Fredrik Nyberg; Anna-Carin Olin; Hanne Krage Carlsen (BMC, 2023)
Abstract Background Air pollution is a large environmental health hazard whose exposure and health effects are unequally distributed among individuals. This is, at least in part, due to gene-environment interactions, but few studies exist. Thus, the current study aimed to explore genetic susceptibility to airway inflammation from short-term air pollution exposure through mechanisms of gene-environment interaction involving the SFTPA, GST and NOS genes. Methods Five thousand seven hundred two adults were included. The outcome measure was fraction of exhaled nitric oxide (FeNO), at 50 and 270 ml/s. Exposures were ozone (O3), particulate matter < 10 µm (PM10), and nitrogen dioxide (NO2) 3, 24, or 120-h prior to FeNO measurement. In the SFTPA, GST and NOS genes, 24 single nucleotide polymorphisms (SNPs) were analyzed for interaction effects. The data were analyzed using quantile regression in both single-and multipollutant models. Results Significant interactions between SNPs and air pollution were found for six SNPs (p < 0.05): rs4253527 (SFTPA1) with O3 and NOx, rs2266637 (GSTT1) with NO2, rs4795051 (NOS2) with PM10, NO2 and NOx, rs4796017 (NOS2) with PM10, rs2248814 (NOS2) with PM10 and rs7830 (NOS3) with NO2. The marginal effects on FeNO for three of these SNPs were significant (per increase of 10 µg/m3):rs4253527 (SFTPA1) with O3 (β: 0.155, 95%CI: 0.013-0.297), rs4795051 (NOS2) with PM10 (β: 0.073, 95%CI: 0.00-0.147 (single pollutant), β: 0.081, 95%CI: 0.004-0.159 (multipollutant)) and NO2 (β: -0.084, 95%CI: -0.147; -0.020 (3 h), β: -0.188, 95%CI: -0.359; -0.018 (120 h)) and rs4796017 (NOS2) with PM10 (β: 0.396, 95%CI: 0.003-0.790). Conclusions Increased inflammatory response from air pollution exposure was observed among subjects with polymorphisms in SFTPA1, GSTT1, and NOS genes, where O3 interacted with SFTPA1 and PM10 and NO2/NOx with the GSTT1 and NOS genes. This provides a basis for the further exploration of biological mechanisms as well as the identification of individuals susceptible to the effects of outdoor air pollution.